NAVIGATING THE AGRICULTURAL LANDSCAPE: THE IMPACT OF CLIMATE ON BANGLADESH’S FARMING PRACTICES - Hasanat, Mohamamad Asrarul; Bhawmick, Sojib; Hasan, Md. Parvez; Roy, Radiant; Islam, Didarul (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
Agriculture in Bangladesh has a significant impact on the economy, contributing 11.37 percent to the national GDP and employing almost 45 percent of the total labor force. Both climatic and non-climatic factors significantly influence the Agricultural productivity in Bangladesh, as the country is highly climate sensitive due to its geographical location. Climate factors (rainfall, Temperature, CO₂ emissions) and non-climate inputs (fertilizer) critically influence agricultural productivity, yet their combined short- and long-term macroeconomic impacts remain underexplored. This study examines the effects of climatic and non-climatic factors on agricultural productivity and their subsequent macroeconomic implications in Bangladesh. Using time series data (1990–2021), we employ the Autoregressive Distributed Lag (ARDL) model to assess long-term elasticities and the Granger causality test to determine directional relationships between variables The ARDL results reveal significant long-term elasticities: a 1% increase in fertilizer use raises agricultural output by 0.49%, while a 1% rise in Temperature reduces output by 0.04%. CO₂ emissions and rainfall show positive impacts (0.71% and 0.96%, respectively). The error correction term (-0.49) indicates the system corrects 49% of short-run disequilibrium annually. Granger causality confirms bidirectional relationships between fertilizer use and agricultural productivity (F-stat = 3.72), while Temperature unidirectionally affects output (F-stat = 4.22). The findings validate that non-climate factors (fertilizer) and climate variables (CO₂, rainfall) positively influence agricultural output, whereas Temperature exerts adverse effects. These results align with prior regional studies but highlight Bangladesh’s unique susceptibility to temperature fluctuations. JEL Classification Codes: C22, O53, Q54, Q10, Q53, F62.